LONG-TERM INFLUENCE OF INTEGRATED NUTRIENT MANAGEMENT ON SOIL FERTILITY CHANGES AND TOTAL UPTAKE UNDER RICE-RICE CROPPING SYSTEM - P.V. GEETHA SIREESHA*, G. PADMAJA; P.C. RAO (The Journal of Research ANGRAU, 2019)
A long-term field experiment was initiated during Kharif, 1989 to study the effect of the combination of organic and inorganic fertilizers on yield, fertility status and uptake pattern of nutrients in rice-rice cropping system. The results pertaining to 2013-14 were presented in this article. The pH values of 1:2.5 soil-water suspensions ranged from 5.3 to 5.9 after harvest of Kharif and Rabi rice, indicating moderately acidic to slightly acidic in reaction.EC decreased slightly from the initial (1.09 dSm-1) and ranged from 0.78 dSm-1 to 0.95 dSm-1 indicating non-saline nature. The highest organic carbon content (1.70% and 1.88%, respectively) was noticed in the treatment receiving 50% RD of NPK + 50% N through FYM in Kharif and Rabi. Application of FYM along with 100% NPK produced significantly higher yields under both Kharif (7402 kg ha-1) and Rabi (7267 kg ha-1) than the application of 100% NPK (7075 and 7150 kg ha-1) and FYM (5777 kg ha-1 and 4533 kg ha-1) alone treated plots. Nutrient uptake (kg ha-1) of straw under Kharifindicated that nitrogen, phosphorus and potassium uptake was higher in T4 with uptake values of 93.5 kg ha-1, 44.9 kg ha-1 and 184.2 kg ha-1, respectively. Application of 100% RD of NPK + FYM @ 5 t ha-1 was effective in increasing grain and straw yield of rice.